Tumor Grade Is Prognostically Relevant Among Mismatch Repair Deficient Colorectal Carcinomas. (December 2018) - Johncilla, Melanie; Chen, Zhengming; Sweeney, Jacob; Yantiss, Rhonda K.
Abstract : Intestinal-type colorectal adenocarcinomas are graded based on extent of glandular differentiation, although mucinous, signet-ring cell, and solid cancers are, by convention, classified as high grade. Mismatch repair-deficient tumors frequently show high-grade histologic features, yet the World Health Organization classifies them as low grade to reflect their favorable prognosis compared with mismatch repair-proficient cancers. Although some mismatch repair-deficient colorectal cancers behave aggressively, few authors have identified features that predict their behavior. We performed this study to determine which histologic features, if any, predicted outcome among mismatch repair-deficient colorectal carcinomas. We identified 116 mismatch repair-deficient colorectal carcinomas, including 77 localized (stage I to II) and 39 advanced (stage III to IV) tumors, and evaluated them for extent of gland formation, extracellular mucin, signet-ring cell differentiation, solid growth, nuclear grade, tumor-infiltrating lymphocytes and tumor budding. Relationships between these features, pathologic stage, and disease-free survival were assessed. We found that high-grade mismatch repair-deficient tumors were more often of advanced stage than low-grade tumors (46% vs. 23%, P =0.01). Disease-free survival was inversely associated with the presence of a dominant high-grade component and tumor budding ( P =0.01 and 0.04, respectively). Predominantly solid tumors, in particular, were significantly associated with decreased disease-free survival compared with low-grade tumors ( P =0.001). Nuclear grade and tumor-infiltrating lymphocytes were not associated with pathologic stage or outcome. We conclude that low-grade mismatch repair-deficient carcinomas present at an earlier stage and pursue a more favorable course than those mostly composed of high-grade elements. These findings suggest that mismatch repair status should not supplant histologic grade in the assessment of colorectal carcinomas.